PROBLEMATIKA KEKERASAN ORANG TUA PADA ANAK USIA SEKOLAH DASAR PERSPEKTIF ISLAM DI DESA PRASUNG, BUDURAN - Irodatul Khasanah; Ainun Nadlif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Primary school-aged children, who are at the concrete operational stage of cognitive development, need a good family environment to help their personality, intelligence and psychological growth. Children often experience violence, both verbal and physical, which can interfere with their mental, emotional and social development. The purpose of this research is to discover and study the different types of violence perpetrated by parents against primary school-aged children and its effects from an Islamic perspective.  This study uses phenomenological methodology as a qualitative approach. Data were collected through interviews and observations in Prasung village, Sidoarjo district. According to the results, around 20 children in the village experienced domestic violence. This violence has significant consequences, causing mental and emotional disturbances in children, such as anxiety and low self-confidence. Parents are also often unaware of the negative effects of their children's actions and still consider corporal punishment as a good way of discipline. In addition, this study emphasises the importance of applying Islamic values in parenting to stop violence and support compassionate education. This research provides an in-depth insight into child abuse. In addition, it is important for parents to be more aware of how their behaviour impacts their children's development. It is hoped that the findings will encourage more positive parenting that is based on humanitarian and religious values.